Magnetically separable Brønsted acid catalyst for the synthesis of Bisguaiacol-F - Tarade, Komal; Rode, Chandrashekhar; Kamble, Sanjay (New Journal of Chemistry, 2025)
Currently, polycarbonates, epoxy resins, and plastics are commercially made from Bisphenol-A. However, BPA-containing materials are well known for causing major health problems and have been banned in several countries. To address this concern, Bisguaiacol-F (BGF) has been developed as a safer and more sustainable alternative to Bisphenol-A. We created a novel sulfonic acid-functionalized, magnetically separable heterogeneous Br & oslash;nsted acid catalyst, [Fe3O4@SiO2-(Pr)3-N-Bu-SO3H][HSO4-], which was successfully utilized for the manufacture of BGF by condensing 37% aq. formaldehyde with two molecules of guaiacol. The main objective for this reaction was to avoid using excess guaiacol while also completing the conversion of both starting components. Surprisingly, our manufactured catalyst promotes the complete conversion of aqueous formaldehyde and guaiacol into regioisomers such as pp `-BGF, mp `-BGF and op `-BGF with 62%, 15%, and 6% selectivity, respectively. Our novel magnetically separable heterogeneous catalyst has improved catalytic activity in terms of starting material conversion and product distribution, which can be attributed to its unique structural characteristics. It contains a pendant -SO3H group that is connected to a lengthy butyl chain, making it conveniently accessible in the reaction. We have created the framework for a promising and environmentally aware approach to the synthesis of Bisguaiacol-F by meticulously optimizing reaction parameters such as time, temperature, reactant molar ratio, and catalyst loading. The catalyst was extensively characterized using acid-base titration, FT-IR, XRD, TGA, and NMR techniques to confirm the structure and reveal remarkable stability and activity. Notably, the catalyst demonstrated recyclability across six consecutive runs, with no noticeable reduction in its effectiveness. The catalytic activity was also tested for guaiacol condensation with a variety of aldehydes to create Bisguaiacol derivatives.